2021
DOI: 10.1007/s10879-021-09492-w
|View full text |Cite
|
Sign up to set email alerts
|

Will We Ever Again Conduct in-Person Psychotherapy Sessions? Factors Associated with the Decision to Provide in-Person Therapy in the Age of COVID-19

Abstract: The COVID-19 pandemic has forced a new reality on the delivery of psychotherapeutic services. Therapists have had to rapidly adapt to telehealth therapy using various video conferencing technologies while working from spaces that were not necessarily designed for delivering therapy sessions. While COVID-19 continues to be present in therapists’ lives and shapes how they provide services, answering the question of whether to meet with clients in person again is a decision laden with complexity and ambivalence. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…Although conversational turn-taking was associated with positive measures of social interaction, it is important to note that we did not identify differences in observed performance and subjective experience measures between the conditions for any of the three tasks. These results are similar to those of prior studies that found no differences in perceived effectiveness and performance in association with virtual interaction [4][5][6][7][8][9] . Thus, our findings that video conferencing affects social interaction at the behavioral level, but not subjective or performance level, may help to clarify some of the inconsistent findings in the literature.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Although conversational turn-taking was associated with positive measures of social interaction, it is important to note that we did not identify differences in observed performance and subjective experience measures between the conditions for any of the three tasks. These results are similar to those of prior studies that found no differences in perceived effectiveness and performance in association with virtual interaction [4][5][6][7][8][9] . Thus, our findings that video conferencing affects social interaction at the behavioral level, but not subjective or performance level, may help to clarify some of the inconsistent findings in the literature.…”
Section: Discussionsupporting
confidence: 90%
“…Research in this area, however, has produced mixed findings as to whether video conferencing has negative, positive, or no impact on the quality of social interaction. Some studies have found that virtual interactions are no different from in-person interactions in terms of perceived effectiveness and performance in administering neuropsychological assessments 5 , psychotherapy 6 , educational activities 7,8 , facilitating social connectedness 9 , and participating in leisure activities such as yoga 4 . In contrast, other studies found that virtual interaction led to or was associated with a reduction in perceived therapeutic skills 10 and reduced memory function in health care workers 11 , a decline in exam performance 12 , and increased communication and management problems in the workplace 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Shklarski et al's. (2021b) mixed‐methods study also identified a shift in psychotherapists' perceptions of online working through continued exposure. The amount of recommended online content varied significantly between the participants, from ‘at least have one lecture on it, about online counselling and how to do it' (D, lines 281‐282), through to ‘I think like 50 50 really, so you can get even practice of doing both' (F, line 115).
a lot of people might be counselling online in the future and a lot of people might need help with this, so let's integrate it into the course and bring out this new perspective.
…”
Section: Resultsmentioning
confidence: 96%
“…It is important to also reflect on the influence of the evaluation being conducted with counselling students working with children and young people. Shklarski et al (2021aShklarski et al ( , 2021b found that participants working with children were less likely to agree that remote and face-to-face therapy can be equally effective due to the additional planning and creativity required to engage children online. Given these noted differences, different results may have been obtained from interviewing adult counselling trainees.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…The possibility to connect from any device permitted an high and constant participation, despite the numerous treatments these patients have to undergo and the agreement with other activities (work and family management). At the moment we haven't got information that say to us if the web is a proposal equivalent to that in presence, but literature about this theme seems to go this way (31)(32) (33).…”
Section: _______________ Discussionmentioning
confidence: 99%